NH2 functionalized MWCNT based self-healing conductive composite for smart sensing - Yeasmin, Rubaya; Thai Duy, Le; Seo, Hyungtak (Chemical Engineering Journal, 2024)
Amino (NH2) functionalized multi-walled carbon nanotubes (MWCNTs) provide superior electrical and mechanical properties, comes at high material cost. The objective of this study is to develop a low-cost, simple, and effective method of NH2-MWCNTs synthesis. To this objective, we have developed in-house NH2 functionalized MWCNTs by reacting with NH4OH using hydrothermal synthesis process. The synthesized NH2-MWCNTs is compared and found compatible to the commercially available one, which is then used to develop self-healing and stretchable (SHS) conductive composite by incorporating into the self-healing supramolecular polymer. The electro-mechanical and self-healing properties of the composite can be tuned by controlling the amount of NH2-MWCNTs loading into the polymer matrix. The optimized composite showed a maximum strength of 286.15 kPa at its maximum strain rate of 410 %, and a high electrical conductivity of 8.23 S cm−1. It is further utilized to demonstrate SHS strain sensor for biomechanical signal detection, which exhibits high sensitivity to human wrist's flexion and extension. Furthermore, it exhibits a high sensitivity with average TCR value of −5.2 % ℃-1 in a wider temperature range (25–100 ℃). Considering the low-cost in-house synthesis approach as well as the developed sensors’ performances, this study will put a paradigm shift within this research field.
Keywords: Conductive composites; Functionalized multi-walled carbon nanotubes; High sensitivity; Low-costs; Multi-walled-carbon-nanotubes; NH2-multi-walled carbon nanotube; Self-healing; Smart sensing; Strain sensors; Stretchable; NH2-MWCNTs; Self-healing; Strain sensor; Stretchable; Temperature sensor